LINGUOCULTURAL PROCESS ORIENTED TRANSLATION - Yuldosheva, Mamura (Журнал иностранных языков и лингвистики, 2023)
Translation is a process of great significance in the modern world and being the basic criteria in communication has become an important issue in language studies. Through this article, it is going to discover important datas about linguocultural process oriented translation. Moreover, facts about the peculiarities of translation process were given.